16S rRNA is a valuable tool in finding bacterial aetiology of community-acquired pleural empyema–a population-based observational study in South Sweden. Issue 3 (4th March 2022) - Hjertman, Jakob; Bläckberg, Jonas; Ljungquist, Oskar
Abstract: Background: The incidence of community-acquired pleural empyema is increasing. Knowledge of the bacterial aetiology is important in order to base recommendations on empirical antimicrobial treatment. The primary aim of the present study was to describe the bacterial aetiology of adult patients with culture proven and/or 16S rRNA-positive community-acquired pleural infection. Methods: We performed a retrospective, population-based observational cohort study in Skåne County, south of Sweden. We included all patients with pleural samples obtained between 1st of January 2011 to 31st of December 2017 in Skåne, south of Sweden, with a positive culture and/or 16S rRNA result. Exclusion criteria were patients with culture-negative and/or 16S rRNA-negative pleural samples, age < 18 years, pleural empyema caused by trauma or iatrogenesis, pleural infection caused by tuberculosis or fungi, simultaneous lung- or abscess of the abdomen and bacterial species considered to be contaminants. Results: A total of 291 patients were included in the study, of which 63% were men and the median age was 69 years. The dominating bacterial aetiology was viridans streptococci (36%), followed by Streptococcus pneumoniae (14%) and anaerobic bacteria (12%). 16S rRNA added information of bacterial aetiology in addition to standard culturing methods in 63% of the patients. Conclusion: We found that the aetiology of adult patients with culture proven and/or 16S rRNA-positive community-acquired pleural empyema is dominated by viridans streptococci, S. pneumoniae and anaerobic bacteria. Our study shows that 16S rRNA is a valuable tool in finding the bacterial aetiology of community-acquired pleural empyema.